Early feeding leads to molecular maturation of the gut mucosal immune system in suckling piglets - Choudhury, Raka; Gu, Yuner; Bolhuis, J. Elizabeth; Kleerebezem, Michiel (Frontiers in Immunology, 2023)
Introduction Diet-microbiota-host interactions are increasingly studied to comprehend their implications in host metabolism and overall health. Keeping in mind the importance of early life programming in shaping intestinal mucosal development, the pre-weaning period can be utilised to understand these interactions in suckling piglets. The objective of this study was to investigate the consequences of early life feeding on the time-resolved mucosal transcriptional program as well as mucosal morphology. Methods A customised fibrous feed was provided to piglets (early-fed or EF group; 7 litters) from five days of age until weaning (29 days of age) in addition to sow’s milk, whereas control piglets (CON; 6 litters) suckled mother’s milk only. Rectal swabs, intestinal content, and mucosal tissues (jejunum, colon) were obtained pre- and post-weaning for microbiota analysis (16S amplicon sequencing) and host transcriptome analysis (RNA sequencing). Results Early feeding accelerated both microbiota colonisation as well as host transcriptome, towards a more “mature state”, with a more pronounced response in colon compared to jejunum. Early feeding elicited the largest impact on the colon transcriptome just before weaning (compared to post-weaning time-points), exemplified by the modulation of genes involved in cholesterol and energy metabolism and immune response. The transcriptional impact of early feeding persisted during the first days post-weaning and was highlighted by a stronger mucosal response to the weaning stress, via pronounced activation of barrier repair reactions, which is a combination of immune activation, epithelial migration and “wound-repair” like processes, compared to the CON piglets. Discussion Our study demonstrates the potential of early life nutrition in neonatal piglets as a means to support their intestinal development during the suckling period, and to improve adaptation during the weaning transition.